Molecular Dynamics Simulations of the "Breathing" Phase Transformation of MOF Nanocrystallites. Issue 11 (16th August 2019) - Keupp, Julian; Schmid, Rochus
Abstract: The displacive phase transformation of metal‐organic frameworks (MOFs), referred to as "breathing, " is computationally investigated intensively within periodic boundary conditions (PBC). In contrast, the first‐principles parameterized force field MOF‐FF is used to investigate the thermal‐ and pressure‐induced transformations for non‐periodic nanocrystallites of DMOF‐1 (Zn2 (bdc)2 (dabco); bdc: 1, 4‐benzenedicarboxylate; dabco: 1, 4‐diazabicyclo[2.2.2]octane) as a model system to investigate the effect of the PBC approximation on the systems' kinetics and thermodynamics and to assess whether size effects can be captured by this kind of simulation. By the heating of differently sized closed pore nanocrystallites, a spontaneous opening is observed with an interface between the closed and open pore phase moving rapidly through the system. The nucleation temperature for the opening transition rises with size. By enforcing the phase transition with a distance restraint, the free energy can be quantified via umbrella sampling. The apparent barrier is substantially lower than for a concerted process under PBC. Interestingly, the barrier reduces with the size of the nanocrystallite, indicating a hindering surface effect. The results demonstrate that the actual free energy barriers and the importance of surface effects for the transformation under real conditions can only be studied beyond PBC. Abstract : Phase transitions of metal organic framworks are usually simulated utilizing small simulation cells and periodic boundary conditions. Herein it is shown that for strongly bistable systems, simulations of large crystallites without spatial periodicity are the only way to access both, the thermodynamics and the kinetics of these first‐order phase transitions.